Analysis of Consumer Satisfaction Levels on Organic Shallots ( Allium Ascalonicum L) In the Garden of the Faculty of Agriculture, University of Nusa Nipa Indonesia - Fransiskus Heronimus Kaja; Yoseph Yakob Da Rato (International Journal of Education, Information Technology, and Others, 2021)
To determine the characteristics of consumers of organic shallots in practical gardens, Faculty of Agriculture, University of Nusa Nipa Indonesia. The design in this research is quantitative. The author uses quantitative data types to process data obtained from the research location. Analysis of the data used in this study using three data analyzes. Descriptive data analysis was used to explain the characteristics of consumers who consume shallots in the gardens of the Faculty of Agriculture UNIPA, Alok District, Sikka Regency. The next analysis, namely the IPA (Importance Porformance Analysis) analysis, is used to analyze consumer satisfaction with product attributes, namely by distinguishing the gap between interests and product performance. The results of this study indicate that the characteristics of organic shallot consumers in the practical gardens of the Faculty of Agriculture, Nusa Nipa Maumere University indicate that the performance of agricultural practice gardens is good enough and meets the expectations of Unipa agricultural garden consumers. Based on 9 attributes that have been researched on 30 respondents of shallot consumers.